The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s13020-018-0191-z
|View full text |Cite
|
Sign up to set email alerts
|

Corni Fructus: a review of chemical constituents and pharmacological activities

Abstract: Cornus officinalis Sieb. et Zucc. is part of the genus Cornus of the family Cornaceae. Ripening and dry fruits (Corni Fructus) are recognized as an essential herb medicine in the traditional Chinese medicine (TCM) and have been widely used for over 2000 years. This review provides a comprehensive summary of Corni Fructus (CF), including the botany, phytochemistry, traditional use, and current pharmacological activities. According to the basic theory of TCM, CF usually participates in various Chinese medicinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(57 citation statements)
references
References 67 publications
(94 reference statements)
3
51
0
1
Order By: Relevance
“…According to Dong et al [ 42 ], thirty tannins have been identified in the fruit of C. officinalis , which is considered to be a rich source of gallotannins and ellagitannins. The groups of Hatano and Okuda have broadly investigated the hydrolyzable tannins as follows: their isolation, identification of their structures, and occurrence of several isomers as a result of anomerization at the glucose cores of tannins in C. officinalis [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to Dong et al [ 42 ], thirty tannins have been identified in the fruit of C. officinalis , which is considered to be a rich source of gallotannins and ellagitannins. The groups of Hatano and Okuda have broadly investigated the hydrolyzable tannins as follows: their isolation, identification of their structures, and occurrence of several isomers as a result of anomerization at the glucose cores of tannins in C. officinalis [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…NF-κB-induced cytokines further stimulate, activate and differentiate lamina propria immune cells, which aggravates the perpetuation of mucosal inflammation. In this review, we find that 55% of Chinese medicines having the abilities of regulating NF-κB expression in macrophages (e.g., SM934, artesunate, aesculin, gallic acid and epicatechin) repress the nucleus translocation and phosphorylation of NF-κBp65, inhibit the protein expressions and phosphorylation of NF-κB, whereas 45% (e.g., berberine, [162][163][164].…”
Section: Dss-induced Colon Tissuementioning
confidence: 99%
“…Протиалергійний прояв кормової добавки ми відстежували за динамікою еозинофілів і станом тварин (свербіж, розчоси) й отримали позитивні результати. Вплив складників кормової добавки попередньо вивчили багато дослідників виявивши їх антитоксичну та протизапальну, нейропротекторну та гепатопротекторну дію (Tanideh et al, 2016;Dong et al, 2018).…”
Section: обговоренняunclassified